Clinical features of poorly distinguishable HFMD and chickenpox in children: a retrospective analysis - Yang, Qiuxia; Zhang, Yiteng; Duan, Jiaxin (Frontiers in Pediatrics, 2025)
Atypical Hand-foot-mouth disease (HFMD), which is caused predominantly by enteroviruses (EVs) shares overlapping cutaneous manifestations with varicella, a condition triggered by varicella-zoster virus (VZV) and further complicates diagnosis. This study systematically characterized the clinical features, hematological profiles, and infection patterns (single, mixed and sequential infection) of pediatric patients with poorly distinguishable EV and VZV infection to improve diagnostic accuracy and optimize clinical management strategies. A retrospective analysis was conducted on the cases that were difficult to distinguish and were confirmed by polymerase chain reaction (PCR) from 2021 to 2025, including demographics, symptoms, hematological profiles, and infection patterns. Among the 85 patients, 33 had a single EV infection and 46 had a single VZV infection, with 4 mixed infections and 2 sequential infections. Compared with patients in the VZV group, those in the EV group were more often associated with local rashes on the limbs and around the mouth, often accompanied by oral vesicles. In contrast, patients with VZV infection usually exhibited pruritic, widespread skin rashes across the body. Virological testing identified CV-A6 as the dominant EV serotype (51.52%). Hematological profiles revealed increased atypical lymphocytes in patients with VZV infection compared with those with EV infection. Patients with mixed infection maybe correlated with more extensive skin lesions. The clinical differentiation of poorly distinguishable EV and VZV infection presents significant challenges, especially in children with mixed infection or atypical features. In the absence of early virological testing, it is hoped that this study can provide some guidance for the diagnosis of HFMD and chickenpox that are difficult to distinguish or have mixed infection.